Psychometric Evaluation of The Walsh Family Resilience Questionnaire (WFRQ) Using the Rasch Model - Al Fatah, Muhammad Qori; Suprananto; Cut Rizka Aliana (Psikoislamedia: Jurnal Psikologi, 2025)
The Walsh Family Resilience Questionnaire (WFRQ) is a widely used instrument for measuring family resilience in various cultural contexts. However, research on its psychometric quality using the Rasch model approach is still limited, especially in Indonesia. This study aims to examine the item fit, unidimensionality, difficulty level, and reliability of the WFRQ by involving 355 adult respondents living with their nuclear or extended families. Data analysis was performed using WINSTEP software. The results show that most WFRQ items meet the fit criteria with Mean Square (MNSQ) values ranging from 0.5 to 1.5. Two items (8 and 20) were eliminated because they did not meet the fit criteria. The reliability value was excellent, with a person reliability of 0.94 and an item reliability of 0.96. The Wright Map showed that the majority of respondents were at a moderate to high level of resilience, while the item difficulty level was relatively low, making the instrument easy for respondents with high resilience.  Keywords: Rasch model, WFRQ, Psychometrics